IMPROVING THE SALES PROCESS OF THE AUTO DEALER ENTERPRISE: HIDDEN POINTS OF GROWTH - E. Kuptsova; E. Kuptsova (Вестник университета)
Sales have been considered as a process, which can be described, studied, systematized and, on this basis, to increase its effectiveness. The results of the audit work of the sales department of the dealership have been presented. The problems of telephone conversations of sellers with dealership customers and the reasons for refusing to buy a car have been revealed. The control points for incoming phone calls from the marketing department and sales department have been defined. An approach to the development of the sales model of an auto dealer center based on lido generation has been considered.